Seismic analysis of arch dams including dam-reservoir interaction via a continuum damage model - Karaton, M; Calayir, Y; Bayraktar, A (Techno-Press, 2006)
In this study, the earthquake damage response of the concrete arch dams was investigated including dam-reservoir interaction. A continuum damage model which is a second-order tensor and includes the strain softening behavior was selected for the concrete material. Fluid-structure interaction problem was modeled by Lagrangian approach. Sommerfeld radiation condition was applied to the truncated boundary of reservoir. The improved form of the HHT-alpha time integration algorithm was used in the solution of the equations of motion. The arch dam Type 5 was selected for numerical application. For the dynamic input, acceleration records of the 10 December 1967 Koyna earthquake were chosen. These records were scaled with earthquake acceleration scale factor (EASF) and then used in the analyses. Solutions were obtained for empty and full reservoir cases. The effects of EASF and damping ratio on the response of the dam were studied.
Keywords: damage model; dam-reservoir interaction; seismic response; arch dam